Information System for Honda Motorcycle Spare Parts Palembang - Nidya Wisudawati; Apriansyah, Apriansyah; Puji Lestari, Jeni (International Journal of Science, Technology & Management, 2022)
In practice, the industrial world that looks the same as the service industry requires the players to do a lot of quality improvement in order to compete. Its development is so rapid that many business actors use special tricks to run their business. Likewise with business actors from motorcycle service and service workshops, namely AHASS SPS Motor Palembang. The supply of spare parts that must always be there when customers need them is the main attraction for every workshop. But in reality, there is no special inventory management technique that can help partman to order spare parts in the following month. Therefore, this study will create a web-based spare part inventory information system that can control the amount of spare part stock and help predict the need for spare parts every month with the forecasting technique used, namely the Weighted Moving Average method. The results given from this system are suggestions of spare part stock forecast results with a user-friendly web-based display so that it can improve partman performance, maintain credibility and optimize workshop cashflow